Answer:
![r^{6}](https://tex.z-dn.net/?f=r%5E%7B6%7D)
Step-by-step explanation:
To make this a bit easier to see, we'll expand that expression.
R to the 9th is just r times itself 9 times. R to the third is r times itself 3 times.
(excuse my bad formatting)
<u>The expression:</u>
<u>r • r • r • r • r • r • r • r • r • 1</u>
r • r • r • 1
Remember, anything and everything has a coefficient or denominator of 1.
So, we can cancel 3 r's from the numerator and denominator.
<u>r • r • r • r • r • r • 1</u>
1
Simplify....
![\frac{1r^{6}}{1}](https://tex.z-dn.net/?f=%5Cfrac%7B1r%5E%7B6%7D%7D%7B1%7D)
That just equals
.
Answer:
c. 1/6
Step-by-step explanation:
I hope it helps you...
Answer:
=
−
±
2
−
4
√
2
x=\frac{-{\color{#e8710a}{b}} \pm \sqrt{{\color{#e8710a}{b}}^{2}-4{\color{#c92786}{a}}{\color{#129eaf}{c}}}}{2{\color{#c92786}{a}}}
x=2a−b±b2−4ac
Once in standard form, identify a, b, and c from the original equation and plug them into the quadratic formula.
6
2
−
5
−
4
=
0
6x^{2}-5x-4=0
6x2−5x−4=0
=
6
a={\color{#c92786}{6}}
a=6
=
−
5
b={\color{#e8710a}{-5}}
b=−5
=
−
4
c={\color{#129eaf}{-4}}
c=−4
=
−
(
−
5
)
±
(
−
5
)
2
−
4
⋅
6
(
−
4
)
√
2
⋅
6
Step-by-step explanation:
Answer:
6
Step-by-step explanation:
treat the ? as an x. you need to get it by itself. but first you should distribute the 8.
8x + 24 = 48 +24
8x+24 = 72
take the 24 and subtract it from 72
8x= 48
now divide both sides by 8
x= 6